Designing Wearable Electronic Textiles to Detect Early Signs of Neurological Injury and Disease: A Review (Journal of Fiber Bioengineering and Informatics, 2021)
Neurological disorders affect the central and peripheral nervous system covering the brain, spinal chord, cranial nerves, nervous system and neuromuscular junction. There is an unsatisfied need for a non-invasive ambient measuring system which can record patients' vital body levels autonomously and in real-time. There is also an acute need to detect diseases at prodromal stages in patients that may carry asymptomatic characteristics of underlying disease. The opportunities offered through innovations in wearable electronic textiles can provide a solution to this by measuring biomarkers for Alzheimer's disease detection, and other neurological disorders, through a non-invasive biosensor that detects protein levels in saliva. This is an area which has large gaps in research around utilising these technologies for early diagnosis of injury, and for differentiating between stages of illness to provide more accurate and bespoke neurological healthcare.
Keywords: Brain injury; Alzheimer's disease; Wearable Electronics; Biosensors